ACTIVITY OF THE PESTICIDE SUMCIDIN ON THE COPEPODS Lernea cypranace AND Tetrahymena corlissi INFECTING OF Cyprinus carpio AND Gambusia affinis FISHES. - Majeed, Majdy F.; Atte, Raaed S.; Banay, Majad A. (Diyala Agricultural Sciences Journal, 2013)
The effecting of the pesticides sumcidin was tested as a control for the copepod L. cypranacea and the protozoa parasitic T. corlissi living in the fish Gambosia affinis and larva of Cyprinus carpio . The concentration used were (0.001, 0.005, 0.001, 0.1, 0.5 and 1.0) mg/L for (6 , 12 , 24 , 48 and 72 ) hours, the results showed that the concentration 0.01 mg/L have a significant effect on the activity of the larval stages and the protozoa parasite T. corlissi . No sign of pathological effect on the G. affinis and the larvae of C. Carpio before 24 hr. but the effect was significant after this time. Changes was clear in liver, muscle and blood of the fish in concentrations ( 0.1 , 0.5 and 1 ) mgŁ hence these concentrations Sumcidin as lethal for the fish and the larva stage .